A Systematic Review of Multidisciplinary Care of Acute Agitation in the Emergency Department: De-escalation, Pharmacology, and Disposition - Al-Dkhail, Khaled Abdul Rhamn; Alhussain, Hussain Hamad Nasser; Alothman, Majed Abdullah Othman; Alhussain, Ibrahim Fahd Abdalazez; Alhussain, Mohammd Hamad Nasser; Al-Sultan, Mohammed Abdulaziz Abdul Mohsen; Alsultan, Hudaib Mohameed; Kaseb, Hassan Ali Mohammed; Abualsayl, Majed Ahmed; Aldowssri, Saeed Obied Saad; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Acute agitation in the emergency department (ED) is a common, high-risk symptom that occurs secondary to diverse psychiatric, medical, substance-related, and psychosocial emergencies. Treatment has historically been reactive in nature, with a focus on physical restraint and involuntary sedation. A contemporary paradigm shift favors a proactive patient-centered multidisciplinary approach to improve safety and outcomes. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">This review synthesizes evidence from 2015 to 2025 to evaluate the efficacy of integrated, multidisciplinary protocols for managing acute agitation. It specifically assesses the roles of nursing de-escalation, physician medical evaluation, pharmacist-informed pharmacology, and social services-led disposition planning. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> An extensive review of the literature was performed, synthesizing research on protocols that officially combine non-pharmacological and pharmacological approaches. Interdisciplinary collaboration and its effects on major clinical, safety, and operational indicators were the focus. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The literature conclusively substantiates that coordinated, team-based protocols significantly enhance patient and staff safety by reducing physical restraints and seclusion. They reduce negative clinical outcomes, enhance adherence to evidence-based standards, and enable more suitable and humane patient dispositions. Success is contingent upon systematized order sets, frequent staff training, and seamless coordination between disciplines. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The optimal care of acute agitation is a multidisciplinary process. Integrated protocols that utilize the unique skill set of nursing, medicine, pharmacy, and social services are superior to the previous fragmented systems and translate into safer, more effective, and more dignified patient care.